KEANEKARAGAMAN, DESKRIPSI DAN KUNCI DETERMINASI Artabotrys R. Br. (Annonaceae) PULAU JAWA DAN KEPULAUAN SUNDA KECIL - Putri, Rina Trihandayani; Rugayah, Rugayah; Sedayu, Agung (Bioma, 2015)
ABSTRACT A taxonomic study of the genus Artabotrys R. Br. (Annonaceae) in Java and the Lesser Sunda Islands was conducted based on morphological characters. The objective of this study is to determine the diversity, describe and make determination key of Artabotrys which found in Java and the Lesser Sunda Islands. The method used in this study is descriptive. This study was conducted on May-June 2015 in the collection room wing B 2nd floor, type room, and Laboratory of Biosystematic Herbarium Bogoriense - Bidang Botani Puslit Biologi LIPI, Cibinong, Bogor, West Java. The result showed that there are three species of Artabotrys in Java and Lesser Sunda Islands. Artabotrys species found in Java, namely A. hexapetalus, A. suaveolens and A. sumatranus, while the species of the Lesser Sunda Islands only A. hexapetalus. Phenetic analysis shows that the species of Artabotrys in Java and the Lesser Sunda Islands are divided into two subgroups. Determination key and descriptions also provided to identify the species of Artabotrys in Java and Lesser Sunda Islands. Artabotrys natural habitat is lowland forest but now lowland forests decreased. This can lead to biodiversity (including Artabotrys) to be reduced, so that conservation need to be done (conservation both on Artabotrys and lowland forest). Keywords : Artabotrys, Annonaceae, diversity, determination key, Lesser Sunda Islands